2019
DOI: 10.1136/gutjnl-2018-317855
|View full text |Cite
|
Sign up to set email alerts
|

Infants born to mothers with IBD present with altered gut microbiome that transfers abnormalities of the adaptive immune system to germ-free mice

Abstract: Background and aimsPrenatal and early life bacterial colonisation is thought to play a major role in shaping the immune system. Furthermore, accumulating evidence links early life exposures to the risk of developing IBD later in life. We aimed to assess the effect of maternal IBD on the composition of the microbiome during pregnancy and on the offspring’s microbiome.MethodsWe prospectively examined the diversity and taxonomy of the microbiome of pregnant women with and without IBD and their babies at multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(99 citation statements)
references
References 55 publications
1
97
0
1
Order By: Relevance
“…Furthermore, we found abnormal levels of faecal bacterial metabolites in one of the healthy parents in two of three families with a child with CD, which could indicate that dysbiosis is a genetically or environmentally determined trait predisposing to intestinal inflammation in CD. [8] This is in agreement with recently published findings by Joossens et al [10] and Torres et al [11] Van Kruiningen correctly pointed out that extraintestinal manifestations of CD, such as in genitalia, lips or oral cavity, might precede or follow luminal disease. "That CD occurs in these locations, where there is no abscessation, fistulas or microbiome attests to the vascular basis of disease".…”
Section: To the Editorsupporting
confidence: 86%
“…Furthermore, we found abnormal levels of faecal bacterial metabolites in one of the healthy parents in two of three families with a child with CD, which could indicate that dysbiosis is a genetically or environmentally determined trait predisposing to intestinal inflammation in CD. [8] This is in agreement with recently published findings by Joossens et al [10] and Torres et al [11] Van Kruiningen correctly pointed out that extraintestinal manifestations of CD, such as in genitalia, lips or oral cavity, might precede or follow luminal disease. "That CD occurs in these locations, where there is no abscessation, fistulas or microbiome attests to the vascular basis of disease".…”
Section: To the Editorsupporting
confidence: 86%
“…Imprinting of the immune system by the microbiota early in life Z Al Nabhani and G Eberl system. Similarly, alterations (dysbiosis) in the maternal microbiota can be transmitted to the offspring and determine immune reactivity in the long term, [34][35][36] an effect that we will discuss in a later chapter. Other compounds of dietary origin, the metabolism of which may be modulated by the microbiota, such as retinoic acid (RA), have significant effects on the developing fetal immune system.…”
Section: A Fetal Time Window?mentioning
confidence: 99%
“…In accordance with this, it has been shown that dysbiosis of the intestinal ecosystem is correlated with a wide variety of diseases, including inflammatory bowel disease, allergy, cancer, autism, and metabolic syndrome (3,(5)(6)(7)(8)(9). Although it is difficult to determine whether such differences in gut microbiota are the cause or the result of these diseases, studies have demonstrated that change in microbiota or specific bacteria is actually involved in the onset, pathogenesis, and prevention of the diseases (10)(11)(12). Therefore, many efforts have been made to prevent the onset or alleviate the symptoms of the diseases by intervention to the gut microbiota (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 87%